The Effect of Risk Factors on the Levels of Chemical Elements in the Tibial Plateau of Patients with Osteoarthritis following Knee Surgery. (25th October 2015) - Lanocha-Arendarczyk, Natalia; Kosik-Bogacka, Danuta Izabela; Prokopowicz, Adam; Kalisinska, Elzbieta; Sokolowski, Sebastian; Karaczun, Maciej; Zietek, Pawel; Podlasińska, Joanna; Pilarczyk, Bogumila; Tomza-Marciniak, Agnieszka; Baranowska-Bosiacka, Irena; Gutowska, Izabela; et al.
Abstract : The aim of this study was to evaluate the aforementioned chemical elements in tibial plateau samples obtained during knee arthroplasty. The gender-specific analysis of chemical element levels in the bone samples revealed that there were statistically significant differences in the concentration of Pb and Se/Pb ratio. The contents of elements in the tibial plateau in the patients with osteoarthritis (OA) can be arranged in the following descending order: F − > K > Zn > Fe > Sr > Pb > Mn > Se > Cd > THg. We observed statistical significant effects of environmental factors including smoking, seafood diet, and geographical distribution on the levels of the elements in tibial bone. Significant positive correlation coefficients were found for the relationships K-Cd, Zn-Sr, Zn-F −, THg-Pb, Pb-Cd, Se-Se/Pb, Se-Se/Cd, Se/Pb-Se/Cd, Pb-Cd/Ca, Cd-Cd/Ca, and F − -F − /Ca· 1000. Significant negative correlations were found for the relationships THg-Se/Pb, Pb-Se/Pb, Cd-Se/Pb, K-Se/Cd, Pb-Se/Cd, Cd-Se/Cd, THg-Se/THg, Pb-Se/THg, Se-Pb/Cd, Zn-Cd/Ca, and Se/Cd-Cd/Ca. The results reported here may provide a basis for establishing reference values for the tibial plateau in patients with OA who had undergone knee replacement surgery. The concentrations of elements in the bone with OA were determined by age, presence of implants, smoking, fish and seafood diet, and sport activity.